Faktor Risiko Penyebab Terjadinya Malaria di Indonesia : Literature Review - Tya Palpera Utami; Hamzah Hasyim; Ummi Kaltsum; Uthu Dwifitri; Yanti Meriwati; Yuniwarti Yuniwarti; Yusro Paridah; Zulaiha Zulaiha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Malaria is one of the leading causes of disease and death worldwide. Around 2.4 billion people are at risk of malaria. In Indonesia, malaria is still a serious public health problem and is often found outside Java and Bali. The risk of malaria is determined by many factors, especially the type of Anopheles mosquito species, human behavior, and the presence of malaria parasites. A change of any of the factors will affect the risk of malaria. The purpose of this study is to see an overview of the problem of malaria the factors that cause malaria and how to prevent and treat malaria in Indonesia and the world. This research method is a descriptive observational study using a literature review design, with databases Google Scholar. The search results that meet the criteria are then analyzed for articles. Malaria is still a disease with high cases in Indonesia every year. Malaria can occur due to several factors. These factors are behavioral factors and community attitudes (night activities, use of mosquito repellent, use of mosquito nets), home environment factors (existence of cattle pens, presence of bushes, and presence of watery rice fields); physical environmental factors of the house (temperature, humidity, the presence of wires in the ventilation, the presence of the ceiling of the house, and the density of the walls of the house).